The Youth Guarantee and Lifelong Guidance / ELGPN Concept Note No.4 - Borbely-Pecze Tibor Bors (European Lifelong Guidance Policy Network Hutchinson Jo, 2013)
This book is a European policy measure designed to support all young people into sustainable employment. Summary, What is Lifelong Guidance and how can it be mobilized to achieve the goals of the new European Youth Guarantee Initiative, The European Youth Guarantee Initiative as a response to persisting high youth unemployment, The Role of Lifelong Guidance within Young Guarantee Initiatives, Tailoring guidance to individual needs, Challenges to effective integration of lifelong guidance with the Youth Guarantee, Emerging experiences linking guidance with Young Guarantee initiatives, Implications for the European Commission and ELGPN member countries, References.